The behavior of cancellous bone from quasi-static to dynamic strain rates with emphasis on the intermediate regime. Issue 7 (3rd May 2016) - Prot, M.; Cloete, T.J.; Saletti, D.; Laporte, S.
Abstract: Previous studies, conducted using quasi-static and dynamic compression tests, have shown that the mechanical strength of cancellous bone is strain rate dependent. However, these studies have not included the intermediate strain rate (ISR) regime (1/s to 100/s), which is important since it is representative of the loading rates at which non-fatal injuries typically occur. In this study, 127 bovine bone specimens were compressed in 3 regimes spanning 8 distinct strain rates, from 0.001/s to 600/s, using three different devices: a conventional quasi-static testing machine, a wedge-bar (WB) apparatus and a conventional split Hopkinson pressure bar (SHPB) implemented with a cone-in-tube (CiT) striker and a tandem momentum trap. Due to the large sample size, a new robust automated algorithm was developed with which the material properties, such as the apparent Young׳s modulus and the yield and ultimate values of stress and strain, were identified for each individual specimen. A statistical summary of the data is presented. Finally, this study demonstrates that results obtained at intermediate strain rates are essential for a fuller understanding of cancellous bone behavior by providing new data describing the transition between the quasi-static and dynamic regimes.